Balanço crítico da Sociolinguística Variacionista no estado de São Paulo e a proposição de uma frente programática de investigação - Gonçalves, Sebastião Carlos Leite [UNESP] (My University, 2012)
In this paper, I present a critical balance of variationist Socilinguistics in the state of São Paulo I comment briefly the information about scientific production of this research area in the state of São Paulo and I show that its recent development in the state does not allows yet the composition of a sociolinguistic picture of the Portuguese spoken in the state of São Paulo. I present results of variationist researches undertaken with speech samples from the countryside. The analysis is based on features of “caipira” speech described by Amaral ([1920] 1976) at the beginning of the twentieth century. Then, I propose recognizing a programmatic front of research as available in Amaral (1976 [1920]), whereby it is possible to advance the knowledge of spoken language not only related to varieties of São Paulo, but also related to Brazilian Portuguese.

Neste trabalho, tenho por objetivo promover um balanço crítico da pesquisa sociolinguística no estado de São Paulo. Para tanto, reúno informações sobre a produção científica nessa área e mostro que seu desenvolvimento recente no estado de São Paulo ainda não permite compor uma fotografia sociolinguística das variedades paulistas do português brasileiro. Tomando por base aspectos da fala caipira descritos por Amadeu Amaral no início do século XX, apresento resultados de pesquisas variacionistas empreendidas com amostras de fala do interior paulista e proponho o reconhecimento de uma frente programática de pesquisa tal como disponível em Amaral ([1920] 1976), como meio para fazer avançar o conhecimento linguístico não só das variedades paulistas, mas do português brasileiro de um modo geral.
A critical balance of variationist sociolinguistic in São Paulo state and a proposition of a research program
Keywords: sociolinguística variacionista; dialeto caipira; português brasileiro; variationist Sociolinguistics; caipira dialect; Brazilian Portuguese